Kaidah yang Berkaitan dengan Kondisi Membahayakan - Zikri, Abdalul; Akmal, Andi Muhammad; Musyahid, Achmad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The fiqh principle of "ad-Dhararu yuzalu" (poverty must be removed), is one of the five main principles in ushul fikih that plays a central role in shaping welfare-oriented Islamic legal policies. This principle asserts that all forms of harm, hardship, and dangerâ€”both to the individual and to societyâ€”must be avoided or eliminated. Through the approach of syariah-evidence from the Qurâ€™an and hadith, as well as an analysis of various derivative rules, this paper explains the forms of mudharat and the mechanisms of syariah in responding to them. Application examples from various fields such as ubudiyah, muamalah, and crime are presented to demonstrate the flexibility of this principle in daily life. This principle is also fundamental in granting rukhsah (legal relief) in emergency conditions, on the principle that an emergency cannot be overcome by another equal or greater emergency. Thus, the principle of â€œad-Dhararu yuzaluâ€ serves as an important guideline in responding to contemporary issues, while demonstrating the solutive and adaptive character of Islamic law to social dynamics.